Appropriations empiriques du genre - Bargel, Lucie; Bessière, Céline; Della Sudda, Magali; Gollac, Sybille; Guyon, Stéphanie; Oeser, Alexandra; Sofio, Séverine (Sociétés & Représentations, 2007)
Keywords: approches et analyses; discipline; histoire; histoire et politique; militance; projet charge mentale; pédagogie; ressour; ressource en ligne; sciences humaines; sexisme; sexualité; sociologie; systèmes d'oppressions; thématiques

Fonction sexuelle masculine et sexualité féminine - Giami, Alain (Communications, 2007)
Major changes have occurred in male and female sexual function/dysfunction research and treatments. Male erectile dysfunction has been re-conceptualized as an organic dysfunction, which marks a dramatic shift from previous conceptions of psychogenic impotence developed during the 60' and the 70's. This shift is based on major scientific discoveries, and pharmacological advances that took place since the early 80's under the influence of North American urologists. The release of sildenafil in 1998 was thecorner stone of a new paradigm of treatments focusing on male penile activity, far remote from any psychological approaches. More recently, the same group of urologists started to reconsider Female Sexual Dysfunction using the same organic/biological model of sexual function. New pharmaceutical products are currently under trial for the treatment of this new category of female sexual disorder. But as opposed to the absence of public adverse reaction to the development of this approach of male function, many voices raised to oppose this new conception of female function. A major discussion took place in the British Medical Journal (2003) stating that female sexual function was not organically driven, but rather determined by the social, psychological and interpersonal context of female sexual activity and relations. One of the major dimension of this discussion opposed the so-called "simplicity" of male sexual function to the "complexity" of female sexual function.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 2000 à aujourd'hui; 2000-2009; angleterre; approches et analyses; cours; discipline; essentialisme; europe; féminisme radical; patriarcat; premier cycle; pédagogie; périodes historiques; recherche; régions géographiques; santé; sciences humaines; sexisme; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques

Le témoin modeste: diffractions féministes dans l'étude des sciences dans Manifeste cyborg et autres essais - Haraway, Donna Jeanne (Manifeste cyborg et autres essais, 2007)
Cette anthologie propose les textes essentiels de Donna Haraway : Cyborg manifesto, Situated knowledge, Teddy bear patriarchy, Ecce homo, Modest witness, Race.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; cours; discipline; discours dominant; patriarcat; point de vue situé; premier cycle; pédagogie; périodes historiques; régions géographiques; savoir situé; sciences humaines; soc2051; sociologie; systèmes d'oppressions; thématiques; travail; états-unis